Where healthcare systems fall short in long-term ostomy care: implications for quality of life, healthcare utilization, and sustainable care pathways - Judith A. Hargreaves; Diego Schaps; Beata Buchelt (Frontiers in Gastroenterology, 2026)
Introduction Ostomy surgery, most commonly following colorectal cancer, can create a lifelong self-management burden affecting physical health, psychological well-being, and daily functioning. This narrative review synthesizes evidence on long-term ostomy self-management, its multidimensional burden, and interventions and care pathway designs that support sustainable patient-centered outcomes. Methods This narrative review was informed by a structured literature search across PubMed/Medline, Embase, Cochrane Library, CINAHL, ClinicalTrials.gov, ICTRP, and Google Scholar (2020–2026), supplemented by ostomy organization resources and some foundational pre-2020 studies. Literature considered for inclusion were observational, cohort, cross-sectional, qualitative and mixed-methods studies, systematic reviews, meta-analyses, and registry analyses. Results 92 primary studies met the eligibility criteria. Nine thematic domains were identified: self-management burden, quality of life (QoL), healthcare utilization, intervention effectiveness, predictive factors, long-term adaptation, lived experience, economic burden, and environmental sustainability. Ostomy complication rates are high: peristomal skin lesions affect 52–75% of patients, and leakage is reported by 27–58%. Structured education pathways increased independent self-care from 8% to 68% at discharge and reduced home nursing reliance from 80% to 50%. Telehealth and continuing care interventions reduced 30-day readmissions from 29% to 14%. Ostomy-related complications are associated with a substantial, long-term economic burden encompassing both direct (hospitalization and outpatient services) and indirect costs (productivity losses). Body image concerns and sexual dysfunction persist among long-term survivors, and real lived experience research identifies continuous cognitive, emotional, and practical burdens that clinical metrics alone do not capture. Environmental sustainability is an emerging dimension of ostomy care, and ostomy-specific evidence remains limited. Conclusion Longitudinal, patient-centered care pathways integrating education, specialist follow-up, psychosocial support, and digital tools have been associated with improved self-management and QoL and with reductions in complications and unplanned healthcare use; these approaches may also help lower the economic and environmental burden of long-term ostomy care.